2023
DOI: 10.2174/1570159x20666220327222921
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Caspase 3 and Caspase 9 Mediated Apoptosis: A Multimodal Therapeutic Target in Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is one of the significant causes of death and morbidity, and it is hence a focus of translational research. Apoptosis plays an essential part in the pathophysiology of TBI, and its inhibition may help overcome TBI’s negative consequences and improve functional recovery. Whereas physiological neuronal death is necessary for appropriate embryologic development and adult cell turnover, it can also drive neurodegeneration. Caspases are principal mediators of cell death due to apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 114 publications
(93 reference statements)
0
18
0
Order By: Relevance
“…Our results showed that the deletion of YTHDF1 could mitigate structural lesions in both brain and gut tissues post-TBI. At the protein level, apoptosis is potentiated [ 32 , 33 , 34 ], marked by upregulated caspase3 [ 35 , 36 , 37 , 38 ], Cleaved caspase-3 [ 39 ] and BAX, as well as downregulated BCL2 [ 40 , 41 ]. Meanwhile, inflammation is enhanced [ 42 ], such as increased CD68 cells [ 42 , 43 , 44 ] and decreased Foxp3-mediated regulatory T cells (Tregs) [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the deletion of YTHDF1 could mitigate structural lesions in both brain and gut tissues post-TBI. At the protein level, apoptosis is potentiated [ 32 , 33 , 34 ], marked by upregulated caspase3 [ 35 , 36 , 37 , 38 ], Cleaved caspase-3 [ 39 ] and BAX, as well as downregulated BCL2 [ 40 , 41 ]. Meanwhile, inflammation is enhanced [ 42 ], such as increased CD68 cells [ 42 , 43 , 44 ] and decreased Foxp3-mediated regulatory T cells (Tregs) [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the hippocampal tissues of BTBR mice, we found alterations in the pro-apoptotic protein caspase-3, which has been identified as a key mediator of physiological neuronal apoptosis [ 47 ]. The cell lymphoma-2 (Bcl-2) family proteins participate in cell apoptosis and play an important role in regulating neuronal apoptosis and axonal degeneration [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is mediated by a caspase (cysteine aspartyl-specific protease) that cleaves target proteins [174]. Caspase protease activity cleaves hundreds of diverse proteins and is essential for apoptosis [175].…”
Section: Cell Death Mechanism Of Synthetic Bile Acid Derivatives In C...mentioning
confidence: 99%